A novel sensitive aptamer-based nanosensor using rGQDs and MWCNTs for rapid detection of diazinon pesticide. Issue 1 (February 2021) - Talari, Fateme Fooladi; Bozorg, Ali; Faridbod, Farnoush; Vossoughi, Manouchehr
Abstract: An optical apta-nanosensor was designed and developed based on reduced graphene quantum dots (rGQDs) and multi-walled carbon nanotubes (MWCNTs) and applied for the selective detection of diazinon as one of the most widely used organophosphorus pesticides. Considering the GQDs and rGQDs high fluorescence emission and optical stability, efficient optical transducers could be designed and precise detection methods could be developed based on such transducers. Herein, by using rGQDs, diazinon specific aptamer, and MWCNTs, a simple economical fluorescence method has been introduced to detect and measure diazinon with the detection limit of 0.4 nM (0.1 µg/L) in the range of 4–31 nM, meeting the specifications and standards set by the European Union and World Health Organization. To assess apta-nanosensor performance, the real application of the novel apta-nanosensor was then validated by detecting and quantifying diazinon in real samples, including tap water, urine, river water, and agricultural runoff water. The obtained results revealed that, due to the lack of binding affinity for the diazinon specific aptamer, the emission recoveries were kept intact in the presence of other pesticides and thereby, the designed apta-nanosensor was able to promptly detect diazinon pesticide with high accuracy and selectivity in real samples. Accordingly, the accurate apta-nanosensor developed in this study provides a sensitive, inexpensive, fast, and portable device for selective detection of diazinon over other pesticides in contaminated regions. The introduced innovative method could also be applied for other pesticides, providing a practical on-site detection approach for real samples of multi pesticides. Graphical Abstract: ga1 Highlights: A novel optical method was introduced for organophosphorus pesticides rapid detection. Fluorescence emission of rGQD was considered to design an efficient transducer. rGQDs, specific aptamer, and multiwall carbon nanotubes were used to measure diazinon. Precise detection of diazinon with detection limit of 0.4 nM was achieved. Using the introduced method, diazinon was promptly detected in real samples.